AT1-receptor autoantibody exposure in utero contributes to cardiac dysfunction and increased glycolysis in fetal mice. (21st November 2020) - Bai, Lina; Wang, Meili; Zhang, Suli; Yue, Mingming; Guo, Yuhao; Wang, Pengli; Liu, Huirong
Abstract: Exposure to adverse factors in utero may lead to adaptive changes in cardiac structure and metabolism, which increases the risk of chronic cardiovascular disease later in life. Studies showed that the angiotensin II type 1 receptor autoantibodies (AT1-AAs) are able to cross the placenta into the circulation of pregnant rodents' embryo, which adversely affects embryogenesis. However, the effects of AT1-AA exposure on the fetal heart in utero are still unknown. In this study, we investigated whether intrauterine AT1-AA exposure has adverse effects on fetal heart structure, function and metabolism. AT1-AA-positive pregnant mouse models were successfully established by passive immunity, evidenced by increased AT1-AA content. Morphological and ultrasonic results showed that the fetal mice on embryonic day 18 (E18) of AT1-AA group have loose and disordered myocardial structure, and decreased left ventricular ejection fraction (LVEF) and left ventricular fractional shortening (LVFS), compared with control groups. The myocardium of AT1-AA group fetal mice on E18 exhibited increased expression of the key molecules in the glycolytic pathway, pyruvate and lactic acid content and ATP production, suggesting that the glycolysis rate was enhanced. Furthermore, the enhanced effect of glycolysis caused by AT1-AA is mainly through the PPARβ/δ pathway. These data confirmed that fetus exposure to AT1-AA in utero developed left ventricular dysfunction, myocardial structural arrangement disorders, and enhanced glycolysis on E18. Our results support AT1-AA being a potentially harmful factor for cardiovascular disease in fetal mice.